Effect of Vaccination on Sexual Behavior of Pandharpuri Buffalo Bulls - Shelar, RR; Gulavane, SU; Savane, MP; Gaikwad, SM; Khumbar, UB; Chaudhari, RJ (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The present investigation was carried out to study the effect of vaccination on the sexual behavior of six Pandharpuri buffalo bulls. The bulls were vaccinated against HS-BQ in July and FMD-I in September and FMD-II in February. The work was divided into four periods, viz., control/pre-vaccination period (Nov-Jan), and post-HS-BQ, FMD-I and FMD-II vaccination periods. Overall mean libido and sexual behavior score of bulls during the pre-vaccination period was 90.76±0.19 percent, which significantly decreased for first three (76.65±2.79 to 79.17±2.39), two (77.50±1.71, 76.67±3.07) and one (79.15±2.71) week after FMD-II, FMD-I, and HS-BQ vaccination, respectively. Mean reaction time (seconds) of bulls during vaccination free period was 46.25±0.14, it increased significantly in first four (59.17±2.01 to 56.67±2.11), three (56.67±2.11 to 57.50±2.14) and one (57.50±2.81) week post-FMD-II, FMD-I, and HS-BQ vaccination, respectively. FMD-II (February) vaccination had a more harmful effect on sexual behavior and reaction time compared to FMD-I (September) vaccination, perhaps due to the succeeding summer season. It was concluded that sexual rest should be recommended for three, two and oneweek post-FMD-II, FMD-I and HS-BQ vaccination, respectively, return to normal sexual behavior in Pandharpuri buffalo breeding bulls.